(untitled) (Journal of the College of Basic Education, 2022)
The present study was aimed to investigate the effect of sustanon (Anabolic Androgenic steroids )and sesame oil on some physiological functions of, Testes of rat that included estimation of testosterone levels.The histopathological study included changes caused by sustanon and sesame oil on testes and skin . The experimental animals included 25 males Sprague-Dawely rats that divided also equally into 5 subgroups (negative control )( ration and water ) , second group (positive control 1 ml/kg B.W Sesame oil low dose ) ; third group ( positive control 2 ml/kg B.W Sesame oil high dose ). Fourth group ( 10 mg/kg B.W sustanon, Low dose ), Fifth group ( 20 mg/kg B.W sustanon ,high dose ). The groups were injected with sustanon , sesame oil weekly for six weeks intramuscularly and were Killed at the end of sixth week . Testosterone level (ng/ml) increased significantly (p<0.05) in 4th and 5th group in comparison with negative control and two groups of positive control ,while increased non significantly ( P>0.05) in both two positive control groups ( sesame oil ). The histopathological changes in the Testes and skins of Rats were characterized by the following :-Testes sections in rats treated with 10 and 20 mg/kg B.W sustanon showed necrosis intra Testicular tubules with presence of few number of sperms ; and absence of others in Luminal seminiferous tubules in comparison with control ., with spermatogonial necrosis . sesame oil ( Low dose , high dose ) showed normal testicular tissue and most testicular tubules contained sperms in high numbers.The skin sections 10 , 20 mg/kg B.W sustanon revealed an increase in the sebaceous glands in dermis with abscent of hair follicles that refered to hair fallen with increasing sebaceous glands in hypodermis , sesame oil ( low dose ) the skin sections revealed shape near normal and contained hair